Increased Frailty in Individuals With Osteoarthritis and Rheumatoid Arthritis and the Influence of Comorbidity: An Analysis of the UK Biobank Cohort. Issue 12 (19th August 2022) - Cook, Michael J.; Verstappen, Suzanne M. M.; Lunt, Mark; O'Neill, Terence W.
Abstract : Objective: To determine the association between osteoarthritis (OA), rheumatoid arthritis (RA), and frailty and to determine whether comorbidities interact with OA and RA to further increase the likelihood of frailty. Methods: Participants of the UK Biobank age 40–69 years at baseline were included. Demographic, lifestyle, and clinical data were collected at baseline and follow‐up in a subset. Frailty was assessed using a frailty index (FI) (continuous) and a modified frailty phenotype (robust, pre‐frail, frail). The association between RA and OA and frailty at baseline and follow‐up was assessed using multiple regression models. We looked at whether comorbidities, including cardiovascular disease, diabetes mellitus, chronic obstructive pulmonary disease, and depression interacted additively with OA and RA to increase the likelihood of frailty. Results: In total, 457, 561 participants contributed data. Those with (versus without) RA (n = 4, 894) and OA (n = 35, 884), respectively, were more likely to be frail (adjusted relative risk ratio 10.7 [95% confidence interval (95% CI) 9.7, 11.7] and 3.4 [95% CI 3.3, 3.6]) and were more likely to have a higher FI at baseline. There was evidence of additive interaction between RA, OA, and common comorbidities increasing the occurrence of prevalent frailty. Among 25, 163 participants included in longitudinal analysis, patients with RA (n = 202) and OA (n = 1, 811) at baseline had an increased adjusted frailty incidence rate ratio (2.8 [95% CI 1.7, 4.6] and 1.7 [95% CI 1.3, 2.1], respectively) and also a higher FI during follow‐up. Conclusion: Individuals with RA and OA are more likely to have, or develop, frailty. Common comorbidities interact with OA and RA to further increase the likelihood of frailty.